A study on the effects of K2ZrF6 as an additive on the microstructure and hydrogen storage properties of MgH2. Issue 12 (11th February 2015) - Halim Yap, F. A.; Mustafa, N. S.; Ismail, M.
<x xml:space="preserve">Abstract</x> It was found that the MgH2 + 10 wt% K2ZrF6 sample started to decompose at around 250 °C, which was 100 °C and lower than in as-milled MgH2. The re/dehydrogenation kinetics had also improved significantly compared to the undoped MgH2.